Music Center Di Pekanbaru Dengan Pendekatan Arsitektur Ekspresionis - Vicky Sonya; Pedia Aldy; Mira Dharma Susilawaty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Music Center in Pekanbaru is a center that accommodates all activities in the field of music, especially modern music and traditional Malay music. The existence of Music Center in Pekanbaru is supported by high public interest in the art of music, this is reinforced by theexistence of several music schools and the many parents who direct their children to attend music lessons or music schools to hone their children's talents from an early age, in addition to frequent holding music concerts with high public enthusiasm for the concert. Music Centerhas the main function as a forum in educational, commercial and recreational activities for visitors, and in social activities as a meeting place for those who are already proficient inmusic with those who will learn about music. This method uses the Expressionist Architecture Approach which creates a building that expresses an emotion and can be felt by people whosee it, so that it not only provides facilities that can enrich one's expression, but also illustrates expressions in terms of architecture that creates a building that looks like a work of art. Expressionist architecture expressed the expression through the three physical elements of the building, namely facade, interior, floor plan and building mass. Through the concept Flow of Melody the building expresses music that is universal in nature with the flow that flows through the melody, so that not only as the main function of musical expressioncan also be seen through the architecture of the building.keywords : Pekanbaru, Music Center, Expressionist Architecture